How the Innate Immune System of the Blood Contributes to Systemic Pathology in COVID-19-Induced ARDS and Provides Potential Targets for Treatment - Nilsson, Bo; Persson, Barbro; Eriksson, Oskar; Fromell, Karin; Hultström, Michael; Frithiof, Robert; Lipcsey, Miklos; Huber-Lang, Markus; Ekdahl, Kristina N. (Frontiers in Immunology, 2022)
Most SARS-CoV-2 infected patients experience influenza-like symptoms of low or moderate severity. But, already in 2020 early during the pandemic it became obvious that many patients had a high incidence of thrombotic complications which necessitated treatment with high doses of low-molecular heparin (typically 150-300IU/kg) to prevent thrombosis. In some patients, the disease aggravated after approximately 10 days and turned into a full-blown acute respiratory distress syndrome (ARDS) -like pulmonary inflammation with endothelialitis, thrombosis and vascular angiogenesis which often requires intensive care treatment with ventilator support. This stage of the disease is characterized by dysregulation of cytokines and chemokines, in particular with high IL-6 levels, and also by reduced oxygen saturation, high risk of thrombosis, and signs of severe pulmonary damage with ground glass opacities. The direct link between the SARS-CoV-2 and the COVID-19-linked lung injury is not clear. However, indirect evidence speaks in favor of a thromboinflammatory reaction, which may be initiated by the virus itself and/or by infected and damaged/apoptotic cells. We and others have demonstrated that life-threatening COVID-19 ARDS is associated with a strong activation of the intravascular innate immune system (IIIS). Support for this notion is that activation of the complement system predicts survival and kidney disease, and, in the case of MBL, also thrombosis. In addition, coagulation system activation with thromboembolism is a common finding and we see that activation of the complement and kallikrein/kinin systems has a prognostic value for predicting patient survival and the necessity for usage of mechanical ventilation. The general properties of the IIIS can easily be translated into mechanisms of COVID-19 pathophysiology. The prognostic value of complement and kallikrein/kinin biomarkers demonstrate that pharmaceuticals which are licensed or have passed the phase I stage are promising candidate drugs for treatment of COVID-19. Such compounds include complement inhibitors eculizumab and AMY-101 (targeting C5 and C3, respectively) as well as kallikrein/kinin inhibitor Firazyr and the bradykinin receptor 2 inhibitor Ecallantide.